Basalt fiber automobile plate spring and preparation method thereof
By activating the hot pressing composite technology of basalt fiber web and chopped basalt fibers and thermoset polyimide, the fatigue life of basalt fiber automotive leaf springs is improved, and the problem of low fiber surface bonding strength in the existing technology is solved, and the further development is achieved. High service life and fatigue performance.
Patent Information
- Application Number
- CN202411408847.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
AI Technical Summary
The existing basalt fiber automotive leaf springs have low fatigue resistance and service life, mainly due to the low bonding strength of the basalt fiber surface. Traditional treatment methods will damage the fiber surface and affect its strength.
Using the hot pressing composite technology of activated basalt fiber web and activated chopped basalt fiber and thermoset polyimide, the roughness of the fiber surface is improved by using γ-aminopropyltriethoxysilane-ethanol solution and silica as activator. and bonding force to prepare basalt fiber automotive leaf springs with high fatigue life.
It effectively improves the fatigue life of basalt fiber automotive leaf springs, avoids screw holes in the spring body, strengthens the adhesion between the fiber and other materials, and extends the service life.
Smart Images

Figure CN119264659A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an automobile leaf spring, in particular to a basalt fiber automobile leaf spring and a preparation method thereof. Background Art
[0002] Automobile leaf springs are indispensable parts of automobiles. Traditional automobile leaf springs are made of steel plates. However, steel plates are heavy and are not conducive to controlling the overall weight of the automobile.
[0003] Basalt fiber is a high-strength material that is widely used in composite materials. However, due to the smooth surface and high inertness of basalt fiber, its bonding strength with other materials is relatively low. The existing method to improve the surface bonding strength of basalt fiber is to use acid or alkali treatment to corrode the surface of basalt fiber, thereby increasing the roughness of the basalt fiber surface. However, this method will damage the surface of basalt fiber, thereby affecting the strength of basalt fiber and further affecting the service life of basalt fiber automotive leaf springs. Summary of the invention
[0004] The main purpose of the present invention is to provide a basalt fiber automobile leaf spring and a preparation method thereof, which solves the technical problems of low fatigue resistance and low service life of the existing basalt fiber automobile leaf spring.
[0005] In order to achieve the above object, the present invention provides a method for preparing a basalt fiber automobile leaf spring, comprising the following steps:
[0006] S1, crushing basalt to obtain basalt particles, melting the basalt particles, and drawing the basalt fibers;
[0007] S2, weaving a plurality of the basalt fibers to obtain coarse basalt fibers, weaving a plurality of the coarse basalt fibers to obtain a basalt fiber mesh, activating the basalt fiber mesh to obtain an activated basalt fiber mesh;
[0008] S3, cutting the coarse basalt fibers and activating them to obtain activated chopped basalt fibers;
[0009] S4, mixing the activated chopped basalt fibers and thermosetting polyimide to prepare a first composite material, and filling the groove of the mold with the first composite material;
[0010] S5, subsequently laying multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material;
[0011] S6, hot pressing the first mixed material and the second mixed material in a mold, and demolding after the hot pressing is completed to obtain a basalt fiber automobile leaf spring.
[0012] Preferably, in step S1, the melting temperature of the basalt particles is 1400-1500° C., and the diameter of the basalt fibers is 15-25 μm.
[0013] Preferably, in step S2, the linear density of the coarse basalt fiber is 2500-3500 tex, and the mesh spacing of the basalt fiber mesh is 0.5-1 mm.
[0014] Preferably, the method for preparing the activated basalt fiber mesh in step S2 comprises the following steps:
[0015] A. soaking the basalt fiber mesh in an activator;
[0016] B. Drying after soaking to obtain activated basalt fiber mesh.
[0017] Preferably, the length of the activated chopped basalt fibers in step S3 is 5 to 8 mm;
[0018] The method for preparing the activated chopped basalt fiber comprises the following steps:
[0019] a. Soak the cut coarse basalt fiber in an activator;
[0020] b. After soaking, the mixture is dried to obtain activated chopped basalt fibers.
[0021] Preferably, the preparation method of the activator is:
[0022] Dissolving γ-aminopropyltriethoxysilane in an ethanol solution to obtain a γ-aminopropyltriethoxysilane-ethanol solution, and adding silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution to obtain an activator;
[0023] Wherein, the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is (7-8):3;
[0024] In the γ-aminopropyltriethoxysilane-ethanol solution, the content of γ-aminopropyltriethoxysilane is 1-2wt%;
[0025] The weight ratio of the silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution is (3-4):100.
[0026] Preferably, in step A, the weight ratio of the basalt fiber mesh to the volume ratio of the activator is (40-50):1;
[0027] The ratio of weight to volume is g:L.
[0028] Preferably, in step a, the weight ratio of the cut coarse basalt fiber to the volume ratio of the activator is (40-50):1;
[0029] The ratio of weight to volume is g:L.
[0030] Preferably, in step S4, the weight ratio of the activated chopped basalt fiber to the thermosetting polyimide is (4-5):1, wherein the ratio is g:g, and the thickness of the first composite material is 4 mm;
[0031] In step S5, the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent thermosetting polyimide layers;
[0032] In step S6, the hot pressing temperature is 180-220° C., the pressure is 15-18 MPa, and the holding time is 60-70 min.
[0033] The present invention also discloses a basalt fiber automobile leaf spring, comprising a spring body and a boss, wherein the spring body has a thickness of 20 mm, a width of 70 mm, and a length of 1200 mm, and a boss is integrally formed in the middle of the spring body, wherein the boss has a thickness of 4 mm, a width of 70 mm, and a length of 120 mm.
[0034] The beneficial effects achieved by the present invention are:
[0035] The present invention uses activated basalt fiber mesh as a skeleton material, which can effectively improve the fatigue life of the basalt fiber automobile leaf spring. The present invention uses activated chopped basalt fiber and thermosetting polyimide as the first composite material to make a spring body boss for connection with the outside of the car, avoiding drilling screw holes on the spring body, and further improving the fatigue life of the basalt fiber automobile leaf spring.
[0036] The invention uses γ-aminopropyltriethoxysilane-ethanol solution and manganese dioxide as activators, does not contain strong acid or strong alkali, and will not damage the surface of basalt fiber. The activator in the invention can interact with the surface of basalt fiber to form fine protrusions on the surface of basalt fiber, thereby increasing the roughness of the basalt fiber surface, enhancing the bonding force between basalt fiber and other materials, and improving the fatigue life of basalt fiber automobile leaf springs. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0038] Figure 1 It is a schematic diagram of a basalt fiber automobile leaf spring disclosed in a specific embodiment of the present invention.
[0039] Description of reference numerals:
[0040] 1. Spring body; 2. Boss. DETAILED DESCRIPTION
[0041] The technical scheme in the embodiment of the present invention is described clearly and completely below in conjunction with the accompanying drawings in the embodiment of the present invention. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0042] The invention discloses a method for preparing a basalt fiber automobile leaf spring, comprising the following steps:
[0043] S1. Crush basalt into basalt particles, melt at 1400-1500° C., and draw after melting to obtain basalt fibers with a diameter of 15-25 μm. Both the drawing equipment and the drawing method are prior art, and the present invention will not repeat them.
[0044] S2. Use a stranding machine to weave multiple basalt fibers into a strand of coarse basalt fiber, the linear density of the coarse basalt fiber is 2500-3500 tex, and then weave the coarse basalt fiber into a basalt fiber mesh with a mesh spacing of 0.5-1 mm, and use an activator to treat the basalt fiber mesh to obtain an activated basalt fiber mesh.
[0045] The method for preparing the activated basalt fiber mesh comprises the following steps:
[0046] A. Soaking the basalt fiber mesh in an activator, wherein the weight of the basalt fiber mesh and the volume ratio of the activator are (40-50) g:1 L, wherein the preparation method of the activator is as follows;
[0047] Dissolving γ-aminopropyltriethoxysilane (hereinafter referred to as KH550) in an ethanol solution to prepare a KH550-ethanol solution, and adding silicon dioxide to the KH550-ethanol solution to prepare an activator;
[0048] The volume ratio of anhydrous ethanol to distilled water in the ethanol solution is (7-8) L:3 L;
[0049] In the KH550-ethanol solution, the content of KH550 is 1-2wt%;
[0050] The weight ratio of silicon dioxide to KH550-ethanol solution is (3-4) g:100 g.
[0051] B. After soaking for 3 hours, dry at 70℃ to obtain activated basalt fiber mesh.
[0052] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 5 to 8 mm, and then activate them according to the following steps:
[0053] a. Soak the cut coarse basalt fiber in the above activator, wherein the weight ratio of the cut coarse basalt fiber to the volume ratio of the activator is (40-50) g:1L.
[0054] b. After soaking for 3 hours, the fiber was dried at 70°C to obtain activated chopped basalt fibers.
[0055] S4, mixing the activated chopped basalt fiber and the thermosetting polyimide in a ratio of (4-5) g:1 g to prepare a first composite material, and filling the first composite material into the groove of the mold, wherein the thickness of the first composite material is 4 mm;
[0056] S5. Lay multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0057] S6. Hot-press the first mixed material and the second mixed material in a mold at a temperature of 180 to 220° C., a pressure of 15 to 18 MPa, and a holding time of 60 to 70 min. After hot-pressing, demolding is performed to obtain a basalt fiber automotive leaf spring.
[0058] like Figure 1 As shown, the present invention also discloses a basalt fiber automobile leaf spring, including a spring body 1 and a boss 2. The spring body 1 is made of the second composite material, the spring body 1 has a thickness of 20 mm, a width of 70 mm, and a length of 1200 mm. A boss 2 is integrally formed in the middle of the spring body 1, and the boss 2 is made of the first composite material. The boss 2 has a thickness of 4 mm, a width of 70 mm, and a length of 120 mm.
[0059] Example 1 A method for preparing a basalt fiber automobile leaf spring
[0060] S1. Crush basalt into basalt particles, melt them at 1400°C, and draw them after melting to obtain basalt fibers with a diameter of 15 μm.
[0061] S2. Using a stranding machine to prepare coarse basalt fibers with a linear density of 2500 tex, weaving the coarse basalt fibers into a basalt fiber mesh with a mesh spacing of 0.5 mm, and treating the basalt fiber mesh with an activating agent to obtain an activated basalt fiber mesh.
[0062] The method for preparing the activated basalt fiber mesh comprises the following steps:
[0063] A. Soak the basalt fiber mesh in an activator, wherein the weight of the basalt fiber mesh and the volume ratio of the activator are 40 g:1 L, wherein the preparation method of the activator is as follows;
[0064] KH550 was dissolved in an ethanol solution (the volume ratio of anhydrous ethanol to distilled water was 7L:3L) to prepare a KH550-ethanol solution (the content of KH550 was 1wt%), and silicon dioxide was added to the KH550-ethanol solution (the weight ratio of silicon dioxide to KH550-ethanol solution was 3g:100g) to prepare an activator;
[0065] B. After soaking for 3 hours, dry at 70℃ to obtain activated basalt fiber mesh.
[0066] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 5 mm, and then activate it according to the following steps:
[0067] a. Soak the cut coarse basalt fibers in the above activator, wherein the weight ratio of the cut coarse basalt fibers to the volume ratio of the activator is 40 g:1 L.
[0068] b. After soaking for 3 hours, the fiber was dried at 70°C to obtain activated chopped basalt fibers.
[0069] S4, mixing the activated chopped basalt fiber and the thermosetting polyimide in a ratio of 4g:1g to prepare a first composite material, and filling the first composite material into the groove of the mold, wherein the thickness of the first composite material is 4 mm;
[0070] S5. Lay multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0071] S6. Hot-press the first mixed material and the second mixed material in a mold at a temperature of 180° C., a pressure of 15 MPa, and a holding time of 60 min. After the hot-pressing is completed, demolding is performed to obtain a basalt fiber automobile leaf spring.
[0072] Example 2 A method for preparing a basalt fiber automobile leaf spring
[0073] S1. Crush basalt into basalt particles, melt them at 1500°C, and draw them after melting to obtain basalt fibers with a diameter of 15 μm.
[0074] S2. Using a stranding machine to prepare coarse basalt fibers with a linear density of 3500 tex, weaving the coarse basalt fibers into a basalt fiber mesh with a mesh spacing of 0.5 mm, and treating the basalt fiber mesh with an activating agent to obtain an activated basalt fiber mesh.
[0075] The method for preparing the activated basalt fiber mesh comprises the following steps:
[0076] A. Soaking the basalt fiber mesh in an activator, wherein the weight of the basalt fiber mesh and the volume ratio of the activator are 50 g:1 L, wherein the preparation method of the activator is as follows;
[0077] KH550 was dissolved in an ethanol solution (the volume ratio of anhydrous ethanol to distilled water was 7L:3L) to prepare a KH550-ethanol solution (the content of KH550 was 2wt%), and silicon dioxide was added to the KH550-ethanol solution (the weight ratio of silicon dioxide to KH550-ethanol solution was 3g:100g) to prepare an activator;
[0078] B. After soaking for 3 hours, dry at 70℃ to obtain activated basalt fiber mesh.
[0079] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 8 mm, and then activate it according to the following steps:
[0080] a. Soak the cut coarse basalt fibers in the above activator, wherein the weight ratio of the cut coarse basalt fibers to the volume ratio of the activator is 40 g:1 L.
[0081] b. After soaking for 3 hours, the fiber was dried at 70°C to obtain activated chopped basalt fibers.
[0082] S4, mixing the activated chopped basalt fiber and the thermosetting polyimide in a ratio of 5g:1g to prepare a first composite material, and filling the first composite material into the groove of the mold, wherein the thickness of the first composite material is 4 mm;
[0083] S5. Lay multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0084] S6. Hot-press the first mixed material and the second mixed material in a mold at a temperature of 180° C., a pressure of 18 MPa, and a holding time of 60 min. After the hot-pressing is completed, demolding is performed to obtain a basalt fiber automobile leaf spring.
[0085] Example 3 A method for preparing a basalt fiber automobile leaf spring
[0086] S1. Crush basalt into basalt particles, melt them at 1450°C, and draw them into fibers after melting to obtain basalt fibers with a diameter of 25 μm.
[0087] S2. Using a stranding machine to prepare coarse basalt fibers with a linear density of 3000 tex, weaving the coarse basalt fibers into a basalt fiber mesh with a mesh spacing of 1 mm, and treating the basalt fiber mesh with an activating agent to obtain an activated basalt fiber mesh.
[0088] The method for preparing the activated basalt fiber mesh comprises the following steps:
[0089] A. Soak the basalt fiber mesh in an activator, wherein the weight of the basalt fiber mesh and the volume ratio of the activator are 45 g:1 L, wherein the preparation method of the activator is as follows;
[0090] KH550 was dissolved in an ethanol solution (the volume ratio of anhydrous ethanol to distilled water was 8L:3L) to prepare a KH550-ethanol solution (the content of KH550 was 1.5wt%), and silicon dioxide was added to the KH550-ethanol solution (the weight ratio of silicon dioxide to KH550-ethanol solution was 4g:100g) to prepare an activator;
[0091] B. After soaking for 3 hours, dry at 70℃ to obtain activated basalt fiber mesh.
[0092] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 6.5 mm, and then activate it according to the following steps:
[0093] a. Soak the cut coarse basalt fibers in the above activator, wherein the weight ratio of the cut coarse basalt fibers to the volume ratio of the activator is 50 g:1 L.
[0094] b. After soaking for 3 hours, the fiber was dried at 70°C to obtain activated chopped basalt fibers.
[0095] S4, mixing the activated chopped basalt fiber and the thermosetting polyimide in a ratio of 4.5 g:1 g to prepare a first composite material, and filling the first composite material into the groove of the mold, wherein the thickness of the first composite material is 4 mm;
[0096] S5. Lay multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0097] S6. Hot-press the first mixed material and the second mixed material in a mold at a temperature of 220° C., a pressure of 16.5 MPa, and a holding time of 70 min. After the hot-pressing is completed, demolding is performed to obtain a basalt fiber automobile leaf spring.
[0098] Example 4 A method for preparing a basalt fiber automobile leaf spring
[0099] S1. Crush basalt into basalt particles, melt them at 1400°C, and draw them after melting to obtain basalt fibers with a diameter of 20 μm.
[0100] S2. A stranding machine is used to prepare coarse basalt fibers with a linear density of 2500 tex, and the coarse basalt fibers are then woven into a basalt fiber mesh with a mesh spacing of 0.75 mm. The basalt fiber mesh is treated with an activating agent to obtain an activated basalt fiber mesh.
[0101] The method for preparing the activated basalt fiber mesh comprises the following steps:
[0102] A. Soak the basalt fiber mesh in an activator, wherein the weight of the basalt fiber mesh and the volume ratio of the activator are 40 g:1 L, wherein the preparation method of the activator is as follows;
[0103] KH550 was dissolved in an ethanol solution (the volume ratio of anhydrous ethanol to distilled water was 7.5 L:3 L) to prepare a KH550-ethanol solution (the content of KH550 was 1 wt%), and silicon dioxide was added to the KH550-ethanol solution (the weight ratio of silicon dioxide to KH550-ethanol solution was 3.5 g:100 g) to prepare an activator;
[0104] B. After soaking for 3 hours, dry at 70℃ to obtain activated basalt fiber mesh.
[0105] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 5 mm, and then activate it according to the following steps:
[0106] a. Soak the cut coarse basalt fiber in the above activator, wherein the weight ratio of the cut coarse basalt fiber to the volume ratio of the activator is 45g:1L.
[0107] b. After soaking for 3 hours, the fiber was dried at 70°C to obtain activated chopped basalt fibers.
[0108] S4, mixing the activated chopped basalt fiber and the thermosetting polyimide in a ratio of 4g:1g to prepare a first composite material, and filling the first composite material into the groove of the mold, wherein the thickness of the first composite material is 4 mm;
[0109] S5. Lay multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0110] S6. Hot-press the first mixed material and the second mixed material in a mold at a temperature of 200° C., a pressure of 15 MPa, and a holding time of 65 min. After the hot-pressing is completed, demolding is performed to obtain a basalt fiber automobile leaf spring.
[0111] Comparative Example 1
[0112] S1. Crush basalt into basalt particles, melt them at 1400°C, and draw them after melting to obtain basalt fibers with a diameter of 15 μm.
[0113] S2. Using a stranding machine to prepare coarse basalt fibers with a linear density of 2500 tex, weaving the coarse basalt fibers into a basalt fiber mesh with a mesh spacing of 0.5 mm, and treating the basalt fiber mesh with an activating agent to obtain an activated basalt fiber mesh.
[0114] The method for preparing the activated basalt fiber mesh comprises the following steps:
[0115] A. Soak the basalt fiber mesh in an activator, wherein the weight of the basalt fiber mesh and the volume ratio of the activator are 40 g:1 L, wherein the preparation method of the activator is as follows;
[0116] KH550 was dissolved in an ethanol solution (the volume ratio of anhydrous ethanol to distilled water was 7L:3L) to prepare a KH550-ethanol solution (the content of KH550 was 1wt%), and silicon dioxide was added to the KH550-ethanol solution (the weight ratio of silicon dioxide to KH550-ethanol solution was 3g:100g) to prepare an activator;
[0117] B. After soaking for 3 hours, dry at 70℃ to obtain activated basalt fiber mesh.
[0118] S3. Lay multiple layers of thermosetting polyimide and the activated basalt fiber mesh in a mold (this mold has no grooves) from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0119] S4. The second mixed material is hot-pressed in a mold at a temperature of 180° C., a pressure of 15 MPa, and a holding time of 60 min. After the hot-pressing is completed, the mold is demoulded to obtain a basalt fiber automobile leaf spring.
[0120] Comparative Example 2
[0121] S1. Crush basalt into basalt particles, melt them at 1400°C, and draw them after melting to obtain basalt fibers with a diameter of 15 μm.
[0122] S2. A stranding machine is used to prepare coarse basalt fibers with a linear density of 2500 tex, and the coarse basalt fibers are then woven into a basalt fiber mesh with a mesh spacing of 0.5 mm.
[0123] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 5 mm, and then activate it according to the following steps:
[0124] a. Soak the cut coarse basalt fibers in the above activator, wherein the weight ratio of the cut coarse basalt fibers to the volume ratio of the activator is 40 g:1 L.
[0125] b. After soaking for 3 hours, the fiber was dried at 70°C to obtain activated chopped basalt fibers.
[0126] S4, mixing the activated chopped basalt fiber and the thermosetting polyimide in a ratio of 4g:1g to prepare a first composite material, and filling the first composite material into the groove of the mold, wherein the thickness of the first composite material is 4 mm;
[0127] S5. Lay multiple layers of thermosetting polyimide and the basalt fiber mesh in the mold from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0128] S6. Hot-press the first mixed material and the second mixed material in a mold at a temperature of 180° C., a pressure of 15 MPa, and a holding time of 60 min. After the hot-pressing is completed, demolding is performed to obtain a basalt fiber automobile leaf spring.
[0129] Comparative Example 3
[0130] S1. Crush basalt into basalt particles, melt them at 1400°C, and draw them after melting to obtain basalt fibers with a diameter of 15 μm.
[0131] S2. Using a stranding machine to prepare coarse basalt fibers with a linear density of 2500 tex, weaving the coarse basalt fibers into a basalt fiber mesh with a mesh spacing of 0.5 mm, and treating the basalt fiber mesh with an activating agent to obtain an activated basalt fiber mesh.
[0132] The method for preparing the activated basalt fiber mesh comprises the following steps:
[0133] A. Soak the basalt fiber mesh in an activator, wherein the weight of the basalt fiber mesh and the volume ratio of the activator are 40 g:1 L, wherein the preparation method of the activator is as follows;
[0134] KH550 was dissolved in an ethanol solution (the volume ratio of anhydrous ethanol to distilled water was 7L:3L) to prepare a KH550-ethanol solution (the content of KH550 was 1wt%), and silicon dioxide was added to the KH550-ethanol solution (the weight ratio of silicon dioxide to KH550-ethanol solution was 3g:100g) to prepare an activator;
[0135] B. After soaking for 3 hours, dry at 70℃ to obtain activated basalt fiber mesh.
[0136] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 5 mm.
[0137] S4, mixing 5 mm thick basalt fiber and thermosetting polyimide in a ratio of 4 g:1 g to prepare a first composite material, and filling the first composite material into the groove of the mold, the thickness of the first composite material is 4 mm;
[0138] S5. Lay multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material, wherein the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent layers of the thermosetting polyimide layers.
[0139] S6. Hot-press the first mixed material and the second mixed material in a mold at a temperature of 180° C., a pressure of 15 MPa, and a holding time of 60 min. After the hot-pressing is completed, demolding is performed to obtain a basalt fiber automobile leaf spring.
[0140] Comparative Example 4
[0141] S1. Crush basalt into basalt particles, melt them at 1400°C, and draw them after melting to obtain basalt fibers with a diameter of 15 μm.
[0142] S2. A stranding machine is used to prepare coarse basalt fibers with a linear density of 2500 tex, and the coarse basalt fibers are then woven into a basalt fiber mesh with a mesh spacing of 0.5 mm.
[0143] S3. Use a cutting tool to cut the coarse basalt fiber into fibers with a length of 5 mm, and then activate it according to the following steps:
[0144] a. Soak the cut coarse basalt fibers in the above activator, wherein the weight ratio of the cut coarse basalt fibers to the volume ratio of the activator is 40 g:1 L.
[0145] b. After soaking for 3 hours, the fiber was dried at 70°C to obtain activated chopped basalt fibers.
[0146] The preparation method of the activator is as follows:
[0147] KH550 was dissolved in an ethanol solution (the volume ratio of anhydrous ethanol to distilled water was 7L:3L) to prepare a KH550-ethanol solution (the content of KH550 was 1wt%), and silicon dioxide was added to the KH550-ethanol solution (the weight ratio of silicon dioxide to KH550-ethanol solution was 3g:100g) to prepare an activator;
[0148] S4, mixing the activated chopped basalt fiber and the thermosetting polyimide in a ratio of 4g:1g to prepare a first composite material, and filling the first composite material into the groove of the mold, wherein the thickness of the first composite material is 4 mm;
[0149] S5. Continue to fill the mold with the first composite material. In this step, the filling thickness of the first composite material is 20 mm.
[0150] S6. Hot-press the first mixed material in a mold at a temperature of 180° C., a pressure of 15 MPa, and a holding time of 60 min. After the hot-pressing is completed, demoulding is performed to obtain a basalt fiber automobile leaf spring.
[0151] According to GB / T19844-2005, fatigue resistance test was carried out on the automobile leaf springs prepared in Examples 1-4 and Comparative Examples 1-4. The results are shown in Table 1.
[0152] Table 1
[0153] Group Fatigue life (10,000 times) Example 1 80.8 Example 2 83.4 Example 3 81.7 Example 4 81.3 Comparative Example 1 62.1 Comparative Example 2 10.3 Comparative Example 3 70.8 Comparative Example 4 53.2
[0154] Referring to Table 1, it can be seen that the basalt fiber automobile leaf springs prepared by the methods in Examples 1-4 all have good fatigue life, while in Comparative Example 1, there is no boss in the middle of the spring body, which reduces the fatigue life of the basalt fiber automobile leaf spring. By comparing Example 1 and Comparative Example 2, it can be seen that the use of unactivated basalt fiber mesh will seriously affect the fatigue life, which may be related to the smoothness of the unactivated basalt fiber mesh and the weak adhesion of thermosetting polyimide. By comparing Example 1 and Comparative Example 3, it can be seen that the use of unactivated coarse basalt fiber for the boss will also affect the fatigue life of the basalt fiber automobile leaf spring. By comparing Example 1 and Comparative Example 4, it can be seen that the activated basalt fiber mesh can further improve the fatigue life of the basalt fiber automobile leaf spring compared to the activated chopped basalt fiber.
[0155] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a basalt fiber automobile leaf spring, characterized in that: The following steps are included: S1, crushing basalt to obtain basalt particles, melting the basalt particles, and drawing the basalt fibers; S2, weaving a plurality of the basalt fibers to obtain coarse basalt fibers, weaving a plurality of the coarse basalt fibers to obtain a basalt fiber mesh, activating the basalt fiber mesh to obtain an activated basalt fiber mesh; S3, cutting the coarse basalt fibers and activating them to obtain activated chopped basalt fibers; S4, mixing the activated chopped basalt fibers and thermosetting polyimide to prepare a first composite material, and filling the groove of the mold with the first composite material; S5, laying multiple layers of thermosetting polyimide and the activated basalt fiber mesh in the mold from bottom to top to obtain a second composite material; S6, hot pressing the first mixed material and the second mixed material in a mold, and demolding after the hot pressing is completed to obtain a basalt fiber automobile leaf spring.
2. The method for preparing a basalt fiber automobile leaf spring according to claim 1, characterized in that: In step S1, the melting temperature of the basalt particles is 1400-1500° C., and the diameter of the basalt fibers is 15-25 μm.
3. The method for preparing a basalt fiber automobile leaf spring according to claim 1, characterized in that: In step S2, the linear density of the coarse basalt fiber is 2500-3500 tex, and the mesh spacing of the basalt fiber mesh is 0.5-1 mm.
4. The method for preparing a basalt fiber automobile leaf spring according to claim 1, characterized in that: The method for preparing the activated basalt fiber mesh in step S2 comprises the following steps: A. soaking the basalt fiber mesh in an activator; B. Drying after soaking to obtain activated basalt fiber mesh.
5. The method for preparing a basalt fiber automobile leaf spring according to claim 1, characterized in that: The length of the activated chopped basalt fibers in step S3 is 5 to 8 mm; The method for preparing the activated chopped basalt fiber comprises the following steps: a. Soak the cut coarse basalt fiber in an activator; b. After soaking, the mixture is dried to obtain activated chopped basalt fibers.
6. The method for preparing a basalt fiber automobile leaf spring according to claim 4 or 5, characterized in that: The preparation method of the activator is: Dissolving γ-aminopropyltriethoxysilane in an ethanol solution to obtain a γ-aminopropyltriethoxysilane-ethanol solution, and adding silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution to obtain an activator; Wherein, the volume ratio of anhydrous ethanol to distilled water in the ethanol solution is (7-8):3; In the γ-aminopropyltriethoxysilane-ethanol solution, the content of γ-aminopropyltriethoxysilane is 1-2wt%; The weight ratio of the silicon dioxide to the γ-aminopropyltriethoxysilane-ethanol solution is (3-4):
100.
7. The method for preparing a basalt fiber automobile leaf spring according to claim 4, characterized in that: In step A, the weight ratio of the basalt fiber mesh to the volume ratio of the activator is (40-50):1; The ratio of weight to volume is g:L.
8. The method for preparing a basalt fiber automobile leaf spring according to claim 5, characterized in that: In step a, the weight ratio of the cut coarse basalt fiber to the volume ratio of the activator is (40-50):1; The ratio of weight to volume is g:L.
9. The method for preparing a basalt fiber automobile leaf spring according to claim 1, characterized in that: In step S4, the weight ratio of the activated chopped basalt fiber to the thermosetting polyimide is (4-5):1, wherein the ratio is g:g, and the thickness of the first composite material is 4 mm; In step S5, the thickness of a single layer of the thermosetting polyimide is 0.5 mm, the topmost layer and the bottommost layer of the second composite material are both thermosetting polyimide layers, the number of thermosetting polyimide layers is 40, and the activated basalt fiber mesh is laid between two adjacent thermosetting polyimide layers; In step S6, the hot pressing temperature is 180-220° C., the pressure is 15-18 MPa, and the holding time is 60-70 min.
10. A basalt fiber automobile leaf spring, characterized in that: It is made by the preparation method of a basalt fiber automobile leaf spring as described in any one of claims 1 to 9, comprising a spring body and a boss, the spring body has a thickness of 20 mm, a width of 70 mm, and a length of 1200 mm, and a boss is integrally formed in the middle of the spring body, the boss has a thickness of 4 mm, a width of 70 mm, and a length of 120 mm.